Bilateral Neck Pyomyositis Caused by Staphylococcus capitis and Staphylococcus saccharolyticus in a Diabetic Adult - Nicholas Young; Hasan Bhally (Case Reports in Infectious Diseases)
We report a case of pyomyositis of the paraspinal neck muscles caused by two coagulase-negative staphylococci: Staphylococcus capitis and Staphylococcus saccharolyticus. Inflammation in the spermatic cords was an additional feature of this infection. Treatment with six weeks of first-generation cephalosporin therapy resulted in complete clinical and radiological resolution.